Post-weaning growth of endemic Iberian wild rabbit subspecies, Orycto lagus cuniculus algirus, kept in a semi-extensive enclosure : implications for management and conservation - Ferreira, A. (2014)
Little is known about the endemic Iberian wild rabbit subspecies, Oryctolagus cuniculus algirus, despite its importance in Mediterranean ecosystems. An individual’s physical condition is of undisputed importance when evaluating the quality of habitats or restocking enclosures to assess the corresponding population status. We analysed post-weaning body weight and growth of 351 individuals of the endemic Oryctolagus cuniculus algirus subspecies under semi-natural conditions in a breeding enclosure in central Portugal. From these data, we described and estimated growth rates for juvenile and adult stages, and 3 sigmoidal growth models were developed. Body weight showed a linear growth of 0.00765 kg/d until 0.6 kg, whereafter it began to decrease steeply until 1 kg (<0.005 kg/d between 0.6 and 0.7 kg, <0.003 kg/d between 0.7 and 0.9 kg, and <0.001 kg/d then on). An age prediction linear growth equation was estimated for individuals up to 0.6 kg. The von Bertalanffy model best described the observed body weight growth. Juvenile body weight growth of Oryctolagus cuniculus algirus is lower than that of the widespread Oryctolagus cuniculus cuniculus. Our data revealed that Oryctolagus cuniculus algirus seems to be smaller, grows less and for less time than Oryctolagus cuniculus cuniculus, according to the literature. Body weight of the studied individuals seems to be more similar to free-living than to cage-bred individuals, according to the literature. These results should provide important indicators to assist managers and conservationists in accessing habitat quality for wild rabbit populations.